Urine Biopsy—Liquid Gold for Molecular Detection and Surveillance of Bladder Cancer - Satyal, Uttam; Srivastava, Abhishek; Abbosh, Philip H. (Frontiers in Oncology, 2019)
With recent advancements in a non-invasive approach to cancer diagnosis and surveillance, the term “liquid biopsy” has gained traction but is currently limited by technological challenges in identifying and isolating circulating tumor cells (CTCs), proteins, cell-free DNA (cfDNA) or other nucleic acids. Tumor tissue biopsy, especially in genitourinary (GU) system is sometimes inadequate and requires invasive surgical options, especially for upper tract urothelial cancer. Urine can prove to be “liquid gold” since it may be a more abundant source of tumor-derived material without the background noise; however, urine DNA (uDNA) may be associated with low mutant allele fraction (MAF). Molecular detection of mutations in uDNA requires a sensitive and accurate method of analysis that allows a high depth of sequencing while minimizing artifacts. Several sequencing approaches to address this hurdle using enhanced library preparation techniques such as Tagged amplicon deep sequencing (TAm-Seq), Safe-SeqS, FAST-SeqS, and CAPP-Seq approaches have been developed. Urine biopsy utilizing next-generation sequencing (NGS) can prove useful at all stages of urologic malignancy care, where urine can be collected to aid in clinical decision making through the identification of commonly known mutations, and potentially reduce or avoid all forms of invasive procedures.